white gene expression, repressive chromatin domains and homeotic gene regulation in Drosophila. - Pirrotta, V.; Rastelli, L. (BioEssays, 1994)
The use of Drosophila chromosomal rearrangements and transposon constructs involving the white gene reveals the existence of repressive chromatin domains that can spread over considerable genomic distances. One such type of domain is found in heterochromatin and is responsible for classical position-effect variegation. Another type of repressive domain is established, beginning at specific sequences, by complexes of Polycomb Group proteins. Such complexes, which normally regulate the expression of many genes, including the homeotic loci, are responsible for silencing, white gene variegation, pairing-dependent effects and insertional targeting.